Highly Efficient UV–Visible Photocatalyst from Monolithic 3D Titania/Graphene Quantum Dot Heterostructure Linked by Aminosilane. (18th September 2019) - Yoon, Hyewon; Lee, Kisung; Kim, Hyojung; Park, Minsu; Novak, Travis G.; Hyun, Gayea; Jeong, Mun Seok; Jeon, Seokwoo
Abstract: As rapidly growing environmental pollution demands the development of efficient photocatalytic materials, tremendous attention has been drawn to TiO2, a widely used photocatalytic material with cost‐effectiveness, stability, and outstanding reactivity. To maximize its photocatalytic efficiency by enhancing the photogenerated charge separation, lowering the intrinsically large bandgap (3.2 eV) of TiO2 is a key problem to be overcome. Herein, a new design is reported for an efficient photocatalyst realized by heterostructuring a 3D nanostructured TiO2 monolith (3D TiO2 ) and graphene quantum dots (GQDs) through using 3‐aminopropyltriethoxysilane (APTES) as a linker. The incorporation of APTES between the TiO2 /GQD interface enables the formation of a charge injection‐type heterostructure, as confirmed by transient absorption spectroscopy, providing improvement of both visible absorption and charge separation. As a result, the heterostructure exhibits a 242% enhanced photocatalytic performance compared to that of nonheterostructured 3D TiO2 under visible irradiation, demonstrating its promising potential for practical photocatalytic applications in environmental remediation. Abstract : A 3D nanostructured TiO2 monolith/graphene quantum dot (GQD) heterostructure is obtained via a 3‐aminopropyltriethoxysilane linker which enables favorable attachment of GQD, resulting in significantly enhanced UV–visible photocatalytic activity. The underlying mechanism is identified to be improve light absorption and efficient charge separation from a suppressed orbital coupling effect.